La coopérative agricole à l’épreuve de la loi OHADA - Dibi, Djibli Vincent (International Journal of Humanities and Social Science Research, 2017)
The OHADA law has an impact on the formation and governance of cooperatives in Sub-Saharan Africa. This impact can be explained as follows: Although already present in the agricultural sector and fought by the original cooperatives, the capitalist spirit is further amplified by the OHADA law which promotes economic operators, supporters of the economy market. By allowing their entry into agricultural cooperatives, without any other trial, with large financial means, these traders and other financiers take control of these structures that were once the preserve of agricultural producers. The agricultural cooperative takes the form of a public limited company in which the power is held by the one with the most shares (shares). In this way, the cooperative becomes a private enterprise like all the others. From now on the various cooperative principles are trampled underfoot to make room for the rules that guide capitalist enterprise.
Keywords: Board of directors; Co-operative society; Cooperative society; Democratic control; Fundamental values; Governance; OHADA; Simplified cooperative society; Social shares

La part sociale coopérative, un exemple de propriété commune - Francoual, Pierre (Revue internationale de l'économie sociale, 2017)
L’émergence de la notion de « bien commun » dans les travaux d’Elinor Ostrom incite le juriste à observer les conditions dans lesquelles peuvent s’établir des formes de propriétés communes. Si de nombreux projets ont vu le jour en ce sens, il convient de faire une place au droit des sociétés coopératives qui constitue une proposition stimulante. La question de la propriété y est, en effet, saisie de manière originale, et confère à ces sociétés un caractère durable et propice aux communs. Mobilisant les attributs classiques de la propriété en droit civil, cet article étudie les liens entre le coopérateur et sa part sociale et montre comment le rapport des personnes aux choses cède la place à un régime juridique soucieux du rapport entre les membres, relativement à la coopérative à laquelle ils participent. Starting from the idea of common-pool resources in the works by Elinor Ostrom, lawyers have been looking at the conditions for establishing forms of common ownership. Many projects have been developed in this area, and cooperative law should be included and presents a stimulating proposal. Cooperative law has a unique way of dealing with the issue of ownership that makes cooperative firms sustainable and suitable for commons. Taking into account the conventional characteristics of ownership in civil law, the article examines the relationship between the cooperative member and the member’s share and shows how the relationship of people to things is superseded by a legal model concerned with the relationship among members in relation to the cooperative to which they belong. El surgimiento de la noción de “bien común” en los trabajos de Elinor Ostrom incita el jurista a estudiar las condiciones de establecimiento de formas de propiedades comunes. Entre numerosos proyectos que han surgido en este sentido, conviene de incorporar el Derecho cooperativo que constituye una propuesta estimulante. En efecto, permite analizar de manera original la cuestión de la propiedad, confiriendo a estas sociedades un carácter sostenible y propicio para los comunes. A través la movilización de los atributos clásicos de la propiedad en derecho civil, el presente artículo analiza los vínculos entre el cooperador y su acción y muestra como la relación de las personas con las cosas es sustituida por un régimen jurídico respetuoso de la relación entre los miembros, en lo que respecta la cooperativa en la que participan.